Vergessen und verloren Die Geschichte der österreichischen Chinastudien - Führer, Bernhard (Projektverlag, 2001)
Lost and Forgotten presents an historical overview of one regional development of Chinese studies / Sinology from the seventeenth century to the present time. The book focuses on the description and evaluation of contributions by scholars who originated from Austria and the Austro-Hungarian monarchy. Contributions that were made in Austria and achievements of emigrants are treated in separate chapters. The account of the development of Chinese studies from the time when Sinology was institutionalised at Vienna University (1972) deals with the institutions involved. Apart from published material, the author also includes a wealth of unpublished research work found in libraries and archives in Austria, the United Kingdom, and the United States. The book incorporates detailed investigations of the source material, descriptions of state-of-the-art research at the time, and a discussion of these contributions in the light of the international Sinological discourse past and present. Book reviews, personal correspondence, discussion of personal affiliations and feuds offer further insights into the intellectual background of these scholars, their aims, concerns and methodological approaches.